The effect of extreme loads on changes in accuracy of the throw and functional indicators of heart rate in handball players - Nikiforova, Olga N.; Markin, Edward V. (Физическое воспитание и студенческий спорт)
High competition among student handball teams forces specialists to look for new approaches to improve the training process. The complexity of such searches is related to the conditions of competitive activity in handball, which proceeds with a variable intensity of neuromuscular stresses, which characterizes extreme loads. To increase the accuracy of hitting the goal and special endurance of handball players, a technique has been developed that simulates loads of variable intensity with specially selected exercises and simulates competitive activity. The purpose of the research is to study dynamics of the throw accuracy and heart rate during extreme physical exertion, simulating competitive activities in handball. The article presents results of the introduction of an experimental technique for the specific construction of training sessions, intensity of which was brought to extremes, both game exercises 4 : 4, 3 : 3 for one half and for the entire playground. During the experiment, the effect of such extreme loads on the accuracy of hits and changes in heart rate during the annual cycle was studied. Effectiveness of the technique has been proven, which contributed to improving the accuracy of shots at the goal for 91 balls, i.e. contributed to an improvement in sports performance by 15% within one year cycle.